2023
DOI: 10.3390/ijerph20032655
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Green Growth Effect of Foreign Direct Investment from the Perspective of Environmental Regulation: Evidence from China

Abstract: The inflow of foreign direct investment (FDI) has both advanced China’s economic development process and influenced the ecological quality of China’s regions. Under the deepening of economic globalization and the continuous deterioration in environmental quality, the correlation mechanism between foreign direct investment, environmental regulation, and economic growth is becoming increasingly complex. Therefore, based on the slacks-based measure (SBM) model and the Global Malmquist-Luenberger (GML) index, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The results of FDI include higher productivity, technological progress, technology transfer, better management, strategic restructuring, marketing skills, which generates technological and economic growth (Boghean & State, 2015;Xiao, Gao, Xu L., Wang, & Wei, 2023). Research by Estrin (2017) shows that government policy (government integrity, tax burden, government spending, fiscal health business, freedom labor freedom, monetary freedom, financial freedom) has an important role in attracting foreign direct institutions (FDI) (Chen, et al, 2021;Minović, Stevanović & Aleksić, 2021).…”
Section: Review Of the Literature And Previous Researchmentioning
confidence: 99%
“…The results of FDI include higher productivity, technological progress, technology transfer, better management, strategic restructuring, marketing skills, which generates technological and economic growth (Boghean & State, 2015;Xiao, Gao, Xu L., Wang, & Wei, 2023). Research by Estrin (2017) shows that government policy (government integrity, tax burden, government spending, fiscal health business, freedom labor freedom, monetary freedom, financial freedom) has an important role in attracting foreign direct institutions (FDI) (Chen, et al, 2021;Minović, Stevanović & Aleksić, 2021).…”
Section: Review Of the Literature And Previous Researchmentioning
confidence: 99%
“…Through an empirical analysis, Ayamba et al found that IFDI is the most important method of technology transfer for investing countries, one which can effectively upgrade the technology of investment inflows and effectively improve local pollution problems [16]. A number of studies have constructed China's green economy index and concluded that foreign direct investment promotes green economic growth through independent innovation and inhibits green economic growth through imitation innovation [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings counter the traditional dichotomy between environmental stewardship and economic growth, suggesting that green technologies and policies can actually bolster economic sustainability. Additionally, research by Xiao et al [11], Lu and Yan [12], and Wang et al [13] emphasizes the importance of foreign direct investment and trade openness in facilitating China's green transition, highlighting the roles of international collaboration and market integration in sustainable development. Nonetheless, China's ongoing dependence on fossil fuels poses a significant challenge to achieving full economic sustainability, as evidenced by studies like those of Sun [14], Ren et al [15], Yang et al [16], and Jiang et al [17], which associate fossil fuel consumption with environmental and economic risks.…”
Section: Introductionmentioning
confidence: 99%